Implementation of the Bengkel Al-Qur’an program in fostering students’ religious character at SD YPWKS II Cilegon - Rizqiyawati, Tria (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
The ability to read the Al-Qur’an is a basic thing that students need to have from an early age. However, in reality, in elementary school itself, there are still many students who have difficulty reading the Al-Qur’an properly and correctly. This difficulty is not only caused by individual factors, but also influenced by various external factors, such as the lack of attention from parents to religious education. The problems that arise are related to the low ability to read the Al-Qur’an, it is necessary to make special efforts to overcome these problems so that every student can have the ability to read the Al-Qur’an. The school provides efforts and solutions through the school program it makes. This Bengkel Al-Qur’an program is one of the programs created by the school as a form of coaching carried out in the teaching of the Al-Qur’an in depth, with the aim of instilling religious values in students and eradicating illiteracy in the Al-Qur’an. This research was conducted at SD YPWKS II Cilegon. The approach used is a qualitative approach with a case study method. Where the data is collected through observation, interviews, and documentation. The results of this study show that there is a planning and strategy carried out by the school in carrying out the Bengkel Al-Qur’an program which includes determining the supervisor of the Bengkel Al-Qur’an, making a schedule of activities, making a student recitation card as a record in reading the Al-Qur’an. Then the implementation of the Bengkel Al-Qur’an program includes reading surah together, followed by students being guided to recite with various variations of methods used by the supervisor. The factor that is an obstacle to the Bengkel Al-Qur’an program is the lack of time allocation. The effectiveness of Bengkel Al-Qur’an program is seen from changes in students’ behavior towards religious values and achievement in reading the Al-Qur’an.